A Study of Magnetic Relaxation in Dysprosium(III) Single‐Molecule Magnets. Issue 26 (21st April 2020) - Ding, You‐Song; Han, Tian; Zhai, Yuan‐Qi; Reta, Daniel; Chilton, Nicholas F.; Winpenny, Richard E. P.; Zheng, Yan‐Zhen
Abstract: Although the development of single‐molecule magnets (SMMs) is rapid, there are only two families of high energy barrier ( U eff ) dysprosium(III) SMMs known so far: the cyclopentadienyl (Cp) family with a sandwich structure and the pentagonal‐bipyramidal (PB) family with D 5 h symmetry. These high‐barrier SMMs, which usually possess U eff >500 cm −1 allow the separate study of the four magnetic relaxation paths, namely, direct, quantum tunnelling, Raman and Orbach processes, in detail. Whereas the first family is chemically more challenging to modify the Cp rings, it is shown herein that the latter family, with the common formulae [DyX 1 X 2 (Leq )5 ] +, such as X 1 /X 2 = − OCMe3, − OSiMe3, − OPh, Cl − or Br − ; Leq =THF/pyridine/4‐methylpyridine, can be readily fine‐tuned with a range of axial and equatorial ligands by simple substitution reactions. This allows unambiguous confirmation that the U eff mainly depends on the identity of X 1 and X 2, rather than on Leq . More importantly, the fitted parameters are barrier dependent. If X 1 is an O donor and X 2 is a halide, 500< U eff <600 cm −1, log τ 0avg (s)=−10.66, log C avg (s −1 K − n )= −5.05, n avg =4.1 and T H =9 K (in which τ 0 is the pre‐exponential factor for the Orbach relaxation process, C and n are parameters used to describe Raman relaxation, and T H is the highest temperature at which magnetic hysteresis is observed). For cases in which both X 1 and X 2 are O donors, 900< U eff <1300 cm −1, log τ 0avg (s)=−11.63, log C avg (s −1 K − n )= −6.03, n avg =4.1 and 18< T H <25 K. Based on these results, it can be further concluded that U eff not only has a linear correlation to the axial Dy−X bond lengths, but also to T H for these PB SMMs. This represents the first systematic study of a family of lanthanide SMMs and derives the first magneto‐structural correlation in Dy SMMs. Abstract : Pyramid scheme : An extended and systematic study of a family of lanthanide single‐molecule magnets (SMMs) with pentagonal‐bipyramidal geometry reveals the relaxation parameters and correlations. The energy barriers correlate with structure, mainly the electronegativity of donor atoms on the axial sites (the axial Dy−X bond lengths), and the energy barriers correlate with the blocking and hysteresis temperatures.